2018
DOI: 10.1016/j.echo.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mechanical Dispersion and Global Longitudinal Strain and Ventricular Arrhythmias in Predialysis and Dialysis Patients

Abstract: LV mechanical dispersion along with LV GLS may be an additional valuable risk marker of VA and SCD in predialysis and dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
(41 reference statements)
6
21
4
1
Order By: Relevance
“…Patients with end-stage kidney disease are observed to be at risk of serious arrhythmias. LV mechanical dispersion is proposed as a risk predictor of fatal arrhythmias in patients with chronic kidney disease (18). Thus, rapid ultrafiltration causing RV mechanical dispersion can have a possible arrhythmogenic influence that should be validated with further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with end-stage kidney disease are observed to be at risk of serious arrhythmias. LV mechanical dispersion is proposed as a risk predictor of fatal arrhythmias in patients with chronic kidney disease (18). Thus, rapid ultrafiltration causing RV mechanical dispersion can have a possible arrhythmogenic influence that should be validated with further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The 2018 report of Hensen et al 39 attempted to explore the relationship between dyssynchrony and mortality by retrospectively evaluating the incidence of ventricular arrhythmia in 250 predialysis and dialysis-dependent patients (CKD 3B-5). Interestingly, 16 of the 250 patients had ventricular arrhythmias (defined as aborted cardiac arrest, documented sustained ventricular tachycardia, or ventricular fibrillation) or sudden cardiac death.…”
Section: Pathophysiology Of Cardiac Fibrosis In Eskdmentioning
confidence: 99%
“…Another possible role of STE in advanced CKD has recently been postulated, with a hypothesis‐generating study showing that LV GLS and LV mechanical dispersion could identify the patients at risk for sudden cardiac death (SCD) due to mixture of scar and fibrous tissue within layers of viable myocardium, despite of relatively preserved LVEF . Both autopsy and CMR studies showed that LV GLS correlated well with increased extend of myocardial fibrosis .…”
Section: Speckle‐tracking Echocardiography (Ste)mentioning
confidence: 99%